Hesiod and the Beginnings of Greek Philosophy
1 online resource.
Keywords: What is the role of Hesiod’s poetry in the beginnings of Greek philosophy? This book explores the question by going beyond the traditional responses that stress either continuities or discontinuities between myth and philosophy. Instead, this volume attempts a reflexive or response-oriented approach, that highlights the active re-appropriation and renewal of Hesiodic thought by the Presocratic philosophers. Its fifteen contributions offer large scale comparisons, historiographical considerations, thematic and generic approaches, and detailed case studies.